EPISTEMOLOGI PENDIDIKAN ISLAM : MELACAK AKAR PEMIKIRAN SYED. M. NAQUIB AL-ATTAS - Salamah Eka Susanti (UNZAH Genggong, 2020)
In the context of finding the ideal Islamic education concept, it is a moral responsibility for Muslim scholars to come up with Islamic theory as a paradigm of educational science. Islam as an educational paradigm has different characteristics from other paradigms that underlie the concept of education. It is a must (a must), especially for scientists who are concerned in the field of education, to reconstruct a paradigm building that can be used as a basis for the education system. The alternative Islamic paradigm is a wise choice in the framework of the foundation of the educational paradigm based on the values ​​of the Qur'an. The paradigmatic or conceptual development of Islamic education has been carried out by both Muslim education experts and scientists. Syed M. Naquib Al-Attas is known as a prominent Muslim scientist and thinker, founder and Rector of ISTAC Kuala Lumpur Malaysia, who has fundamental thoughts about the concept of Islamic education. Among the fundamental educational concepts of Syed M. Naquib Al-Attas, which is presented in this paper, is his concept of ta'dib. For him, the fundamental problem in Islamic education is the loss of ethical values ​​in a broad sense. This is due to the unclear understanding of the concepts of tarbiyah, ta'lim and ta'dib. Syed M. Naquib Al-Attas prefers to use the term ta'dib for the concept of Islamic education, because if the concept of ta'dib is applied comprehensively, integrally, and systematically in Islamic education practice, various problems in developing Muslim human resources are expected to be resolved. The basic reason for the application of the concept of ta'dib is adab is closely related to science, because science cannot be taught or transmitted to students unless the person has proper etiquette towards science in various fields. The concept of Islamic education which is only limited to the meanings of tarbiyah and ta'lim has been penetrated by a Western view of life which is based on the values ​​of dualism, secularism, humanism and Sufism so that the values ​​of adab become increasingly blurred and further away from the values ​​of divine wisdom. The reconstruction of the concept of Islamic education carried out by Syed M. Naquib Al-Attas aims to restore Islamic education that has been contaminated and interfered with by the concept of secular Western education to the concept of education that is in accordance with Islamic ideals that have existed since the Prophet Muhammad SAW was sent as an Apostle. The concept of ta'dib which was formulated by Syed M. Naquib Al-Attas, really has high relevance and significance to be implemented in the world of education. Because basically it is an educational concept that intends to integrate the dichotomy of science, maintain equilibrium, have moral and religious characteristics. Key Words: Epistemology, Education, Islamic, Thought.